Improved phase change material structure and preparation method
Through the alternating deposition technology of phase change material layer and dielectric film layer, the refractive index unevenness and mass density changes of phase change materials in crystal state are solved, and the large-area refractive index uniform distribution is achieved, and the phase change material is improved performance and scope of application.
Patent Information
- Application Number
- CN202411357458.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-31
AI Technical Summary
The existing phase change materials have birefringence effects in crystalline state, resulting in uneven refractive index, and the mass density of the material changes greatly during the phase change process, affecting the stability and application range of thin-film devices, and it is difficult for the prior art to control the refractive index. Distribute the area evenly and expand its area.
Using the structure of the substrate layer, phase change material layer and dielectric film layer, the phase change material layer is layered and the dielectric film layer is filled between each phase change material layer, and alternately deposition is used by chemical vapor deposition or physical vapor deposition method. The phase change material layer and the dielectric film layer control the thickness of each phase change material layer and the dielectric film layer to form a large area of uniform refractive index.
Effectively reduce the grain size of phase change materials in crystalline state, improve refractive index unevenness, improve the performance of phase change materials, reduce device manufacturing costs, expand application range, reduce stress accumulation, and extend service life.
Smart Images

Figure CN119233749A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of phase change materials, and in particular to an improved phase change material structure and a preparation method. Background Art
[0002] Phase change material is a material whose internal structure changes with temperature. Under external thermal and electrical stimulation, the internal temperature of the phase change material continues to rise. When the temperature is greater than a certain threshold, the material will change from amorphous to crystalline, accompanied by changes in the physical properties of the phase change material such as refractive index, absorptivity, and mass density. When the temperature exceeds the melting point of the phase change material, the material is quickly cooled to room temperature, and the material will return from crystalline to amorphous, and the physical properties of the material will return to their original state. In this way, under the stimulation of external conditions, the phase change material can cyclically change between the crystalline and amorphous states, and its physical properties also undergo non-volatile alternating changes between the two states. The speed of change between the crystalline and amorphous states of phase change materials can reach the nanosecond level, so they are widely used in technical fields such as dynamic display and reconfigurable photonic devices.
[0003] Sb 2 S 3 , Sb 2 Se 3 As an emerging phase change material, it has the characteristics of large refractive index change in the visible light band (Δn=1 at 600nm) and small absorption (k=0.1~0.7 at 600nm). It is an ideal phase change material for the visible light to near-infrared band. The refractive index change before and after the phase change can be used to realize a variety of reconfigurable photonic devices. However, this type of phase change material currently has two major defects: 1. In the crystalline state, the phase change material exhibits a birefringence effect, that is, there are two grains with different refractive indices (grain size is about 10~30μm), resulting in uneven refractive index distribution in the crystalline state, making it difficult to apply in the field of micro-nano photonic devices; 2. The mass density of this type of material changes greatly before and after the phase change (20%), which will cause the film morphology to deform before and after the phase change, affecting the stability and robustness of the thin film device. The above two shortcomings will seriously affect the application performance and service life of the phase change material, and therefore will greatly limit the application scope of photonic devices based on phase change materials. The current measure is to deposit a 10-200 nm thick dielectric protection film on the phase change material by magnetron sputtering, which can improve the film deformation problem of the phase change material during the phase change process and increase the phase change life of the phase change material.
[0004] Typically, PCMs-based devices are in the form of thin films or patterned thin films. Some PCMs (such as Sb 2 S 3 , Sb 2 Se 3) In the crystalline state, due to the anisotropy of its crystal structure, there is birefringence. The refractive index of grains with different orientations is different, and the orientation distribution of crystals at different positions is disordered, which is manifested as the refractive index changes with position and is unevenly distributed in the film form. This phenomenon poses a challenge to the design and implementation of PCMs devices. The patent CN112736197A provides a method for improving phase-changing materials. It discloses that by coating a protective layer on a PCMs film or a patterned film and selecting a suitable protective material, the area of the single grain orientation in the film is expanded from 10 to 30 μm to more than 400 μm, breaking through the obstacles to device design and implementation caused by the uneven refractive index caused by birefringence. However, there are still two problems in practical applications: 1. The position of the uniform refractive index area cannot be controlled; the formation of the same grain orientation area requires uniform and stable environmental conditions. The uneven distribution of PCMs elements and defects in the protective layer film may break the formation conditions. These factors are difficult to control, resulting in the position of the same grain orientation area usually being distributed in a disorderly manner and uncontrollable, which brings about problems in finding uniform areas and alignment during device manufacturing; 2. The area of the uniform refractive index distribution area is not enough; although the area of the uniform refractive index distribution area has been expanded by an order of magnitude, it is still not enough. Some devices that require millimeter-scale uniform refractive index areas, such as color displays and large-aperture super lenses, still cannot be met. These two existing problems undoubtedly increase the manufacturing cost of PCMs devices and limit their application scope. Summary of the invention
[0005] In order to overcome the above-mentioned defects of the prior art, the present application provides an improved phase change material structure and preparation method which can obtain a large area of uniform refractive index by layering the PCMs film, thereby greatly reducing the production and preparation costs of PCMs devices.
[0006] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: an improved phase change material structure and method, comprising a substrate layer, a phase change material layer and a dielectric film layer; the phase change material layer is located above the substrate layer, the dielectric film layer is located above the phase change material layer, and when the thickness of the phase change material layer is higher than 65nm, the phase change material layer is layered, and the dielectric film layer is filled between the layered phase change material layers; the total thickness of the phase change material layer is 0-5000nm; the thickness of each dielectric film layer is 0-5000nm.
[0007] Preferably, the substrate layer is one or more of an ordinary glass sheet, a fused quartz sheet, a single crystal silicon sheet, and a substrate coated with a thin film.
[0008] Preferably, the phase change material layer is a mixture or compound consisting of two or more elements of Sb, S and Se.
[0009] Preferably, the phase change material layer further includes an X element, and the X element includes one or more elements selected from the group consisting of In, Bi, Ag, Al, Zn, Co, Ni, Cu, Sn, O, Ge, and Te.
[0010] Preferably, the material of the dielectric thin film layer is one or more of oxide, nitride or sulfide.
[0011] Preferably, the material of the dielectric thin film layer is Al 2 O 3 、SiO 2 、 2 O 5 、ZrO 2 、TiO 2 , HfO 2 , tin-doped indium oxide (ITO), aluminum-doped zinc oxide (AZO), ZnS, TiN or Si 3 N 4 One or more of .
[0012] A method for preparing an improved phase change material structure comprises the following steps:
[0013] (1) Cleaning the substrate: preparing a substrate layer, placing the substrate layer in containers containing acetone, ethanol, and ultrapure water in turn for ultrasonic cleaning to remove impurities on the substrate layer;
[0014] (2) Design of phase change material layer: Design the number of phase change material layers according to the thickness of the phase change material film. When the thickness of the phase change material film exceeds 65 nm, the phase change material film is layered to obtain a phase change material layer.
[0015] (3) Depositing a phase change material layer and a dielectric film layer according to the design of the phase change material layer: using chemical vapor deposition or physical vapor deposition to alternately deposit phase change material layers and dielectric film layers on the cleaned substrate, and a dielectric film layer is provided on top of each phase change material layer, the thickness of each phase change material layer does not exceed 65nm, the total thickness of the phase change material layer is 1-5000nm, and the thickness of each dielectric film layer is 1-5000nm.
[0016] A method for preparing an improved phase change material structure comprises the following steps:
[0017] (1) Cleaning the substrate: preparing a substrate layer, placing the substrate layer in containers containing acetone, ethanol, and ultrapure water in turn for ultrasonic cleaning to remove impurities on the substrate layer;
[0018] (2) Patterning: Spin-coating the photoresist on the cleaned substrate layer with a coating machine, and exposing or photolithography the photoresist on the substrate layer through an electron beam exposure or photolithography process to obtain a pattern with a specific structure;
[0019] (3) Phase change material layer design: The number of phase change material layers is designed according to the thickness of the phase change material film. When the thickness of the phase change material film exceeds 65 nm, the phase change material film is layered to obtain a phase change material layer.
[0020] (4) Depositing a phase change material layer and a dielectric film layer according to the design of the phase change material layer: using chemical vapor deposition or physical vapor deposition to alternately deposit phase change material layers and dielectric film layers on a patterned substrate layer, and providing a dielectric film layer on top of each phase change material layer, wherein the thickness of each phase change material layer does not exceed 65 nm, the total thickness of the phase change material layer is 1-5000 nm, and the thickness of each dielectric film layer is 1-5000 nm;
[0021] (5) Stripping: Prepare the debonding agent, isopropyl alcohol and ultrapure water required for stripping, immerse the substrate on which the phase change material is deposited in step (3) in the debonding agent, and ultrasonically strip off the excess photoresist and other process residues on the substrate layer in an ultrasonic cleaning machine to obtain a patterned phase change material; then immerse the patterned phase change material in an isopropyl alcohol solution and ultrapure water in turn to remove the residual debonding agent solution.
[0022] A method for preparing an improved phase change material structure comprises the following steps:
[0023] (1) Cleaning the substrate: preparing a substrate layer, placing the substrate layer in containers containing acetone, ethanol, and ultrapure water in turn for ultrasonic cleaning to remove impurities on the substrate layer;
[0024] (2) Design of phase change material layer: Design the number of phase change material layers according to the thickness of the phase change material film. When the thickness of the phase change material film exceeds 65 nm, the phase change material film is layered to obtain a phase change material layer.
[0025] (3) Depositing a phase change material layer and a dielectric film layer according to the design of the phase change material layer: using chemical vapor deposition or physical vapor deposition to alternately deposit phase change material layers and dielectric film layers on the cleaned substrate, and a dielectric film layer is provided on top of each phase change material layer, the thickness of each phase change material layer does not exceed 65 nm, the total thickness of the phase change material layer is 1-5000 nm, and the thickness of each dielectric film layer is 1-5000 nm;
[0026] (4) Patterning: Spin-coating a photoresist onto a substrate layer on which a phase change material layer and a dielectric film layer are deposited using a coating machine, and exposing or photolithography the photoresist on the substrate layer by electron beam exposure or photolithography to obtain a pattern having a specific structure;
[0027] (5) Etching: using the photoresist pattern produced in step (4) as a mask, and performing an etching process to obtain a patterned phase change material;
[0028] (6) Stripping: Prepare the debonding agent, isopropyl alcohol and ultrapure water required for stripping, immerse the substrate on which the phase change material is deposited in step (5) in the debonding agent, and ultrasonically strip off the excess photoresist and other process residues on the substrate layer in an ultrasonic cleaning machine to obtain a patterned phase change material; then immerse the patterned phase change material in an isopropyl alcohol solution and ultrapure water in turn to remove the residual debonding agent solution.
[0029] Preferably, the dielectric thin film layer is deposited by chemical vapor deposition or physical vapor deposition; chemical vapor deposition and physical vapor deposition methods include: atmospheric pressure chemical vapor deposition, low pressure chemical vapor deposition, plasma enhanced chemical vapor deposition, metal organic chemical vapor deposition, photochemical vapor deposition, atomic layer deposition, evaporation or ion plating.
[0030] The above technical solution of the present invention has the following beneficial effects:
[0031] 1. It can effectively reduce the grain size of phase change materials in the crystalline state, improve the refractive index inhomogeneity caused by the birefringence effect of the grains, and improve the performance of the phase change materials.
[0032] 2. Obtaining a large area with uniform refractive index distribution reduces the design and manufacturing costs of phase change material devices and effectively expands the application scope of phase change materials.
[0033] 3. Reduce the stress accumulation of phase change materials after film formation to avoid deformation, and the method is simple and low-cost.
[0034] 4. Protect the phase change material from the influence of the outside air, prevent the chemical reaction between the outside atmosphere and the phase change material during long-term work, and increase the service life of the phase change material. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a structural schematic diagram of the improved phase change material structure in the present invention;
[0036] Figure 2 is a schematic flow chart of a method for preparing an improved phase change material structure in an embodiment of the present invention;
[0037] Figure 3 is a schematic flow chart of another method for preparing an improved phase change material structure according to an embodiment of the present invention;
[0038] Figure 4 This is a photo of the effect of a phase change material made in a comparative example of the present invention under a microscope;
[0039] Figure 5 This is a photo of the effect of a phase change material made according to an embodiment of the present invention under a microscope. DETAILED DESCRIPTION
[0040] The present invention will be further described below in conjunction with the accompanying drawings and implementation modes.
[0041] Example 1
[0042] like Figure 1 An improved phase change material structure shown includes a substrate layer 3, a phase change material layer 2 and a dielectric film layer 1; the phase change material layer 2 is located above the substrate layer 3, the dielectric film layer 1 is located above the phase change material layer 2, and when the thickness of the phase change material layer 2 is higher than 65nm, the phase change material layer 2 is layered, and the dielectric film layer 1 is filled between the layered phase change material 2 layers; the total thickness of the phase change material layer 2 is 0-5000nm; the thickness of each dielectric film layer 1 is 0-5000nm. The thickness of the dielectric film layer 1 in this embodiment is ≤25nm.
[0043] In this embodiment, the substrate layer 3 is one or more of an ordinary glass sheet, a fused quartz sheet, a single crystal silicon sheet, and a substrate coated with a thin film. Specifically, a fused quartz sheet is used, and the size is 10mm*10mm*1mm;
[0044] The phase change material layer in this embodiment is a mixture or compound of two or more elements of Sb, S, and Se. Specifically, Sb 2 S 3 and / or Sb 2 Se 3 .
[0045] In another embodiment, the phase change material layer further includes an X element, and the X element includes one or more elements of In, Bi, Ag, Al, Zn, Co, Ni, Cu, Sn, O, Ge or Te.
[0046] In one embodiment, the material of the dielectric film layer is one or more of oxide, nitride or sulfide.
[0047] Specifically, the material of the dielectric film layer can be Al 2 O 3 、SiO 2 、 2 O 5 、ZrO 2 、TiO 2 , HfO 2 , tin-doped indium oxide (ITO), aluminum-doped zinc oxide (AZO), ZnS, TiN or Si 3 N 4 One or more of .
[0048] The phase change material provided in this embodiment can improve the refractive index non-uniformity caused by the grain birefringence effect, improve the performance of the phase change material, reduce the stress accumulation of the phase change material after film formation, avoid deformation, and the method is simple and low-cost.
[0049] Example 2
[0050] A method for preparing an improved phase change material structure comprises the following steps:
[0051] (1) Cleaning the substrate:
[0052] Prepare a fused quartz sheet with a size of 10mm*10mm*1mm, place the fused quartz sheet in containers containing acetone, ethanol, and ultrapure water in turn, and ultrasonicate them in an ultrasonic cleaner for 20 minutes (ultrasonicate for 20 minutes in all three media) to remove impurities on the fused quartz sheet, and the cleaning of the substrate layer 3 is completed.
[0053] (2) Layered design of phase change material film: Based on the required thickness of the phase change material film, 65nm is used as the limit: when it is less than 65nm, there is no need to divide the thickness; when it exceeds 65nm, the film is divided into equal thicknesses to form phase change material layers, so that the thickness of the phase change material layer 2 does not exceed 65nm, and the dielectric film layer 1 is used to fill the gaps between the phase change material layers 2.
[0054] (3) Deposition of phase change materials and dielectric films:
[0055] Preparation of phase change material Sb 2 S 3 Powder, Sb deposited by thermal evaporation 2 S 3 The film was deposited on a cleaned fused quartz substrate with a vacuum of 8.0×10 -4 Pa, the deposition rate is about The deposition thickness is about 65nm, and the phase change material deposition is completed.
[0056] Using sputtering method, Sb 2 S 3 SiO deposition on the film surface 2 Thin film, vacuum degree is 8.0×10 -4 Pa, the argon flow rate during deposition is about 100 sccm, the pressure is 0.6 Pa, the sputtering power is about 200 W, and the deposition rate is about The deposition thickness is about 25nm, and the dielectric film deposition is completed. Repeat the above two coating processes, and the number of repetitions is determined according to the required thickness of the phase change film.
[0057] The final formation is Figure 1 The structure shown.
[0058] Example 3
[0059] A method for preparing an improved phase change material structure, such as Figure 2 The following steps are shown:
[0060] (1) Cleaning the substrate:
[0061] Prepare a single crystal silicon wafer with a size of 5mm*5mm*0.55mm, place the single crystal silicon wafer in containers containing acetone, ethanol, and ultrapure water in turn, and ultrasonicate them in an ultrasonic cleaning machine for 20 minutes (ultrasonicate for 20 minutes in all three media) to remove impurities on the single crystal silicon wafer, and the cleaning of the substrate layer 3 is completed.
[0062] (2) Make a pattern:
[0063] Prepare chemical agents such as photoresist, developer, and fixer, and use a coating machine to spin-coat the photoresist (positive photoresist, AR-P 6200) on the surface of the cleaned single-crystal silicon wafer at 4000 rpm. The silicon wafer with the spin-coated photoresist is subjected to electron beam exposure, development, and fixing process steps to obtain a pattern with a specific structure, and the pattern production is completed.
[0064] (3) Phase change material layer design: Based on the required thickness of the phase change material film, 65 nm is used as the limit: when it is less than 65 nm, there is no need to divide the thickness; when it exceeds 65 nm, the film is divided into equal thicknesses to form a phase change material layer 2, so that the thickness of the phase change material layer 2 does not exceed 65 nm, and the phase change material layers 2 are filled with a dielectric film layer 1.
[0065] (4) Deposition of phase change materials and dielectric films:
[0066] Preparation of phase change material Sb 2 S 3 Powder, Sb deposited by thermal evaporation 2 S 3 The film was deposited on a cleaned fused quartz substrate with a vacuum of 8.0×10 -4 Pa, the deposition rate is about The deposition thickness is about 65nm, and the phase change material deposition is completed.
[0067] Using sputtering method, Sb 2 S 3 SiO deposition on the film surface 2 Thin film, vacuum degree is 8.0×10 -4 Pa, the argon flow rate during deposition is about 100 sccm, the pressure is 0.6 Pa, the sputtering power is about 200 W, and the deposition rate is about The deposition thickness is about 25nm, and the dielectric film deposition is completed. Repeat the above two coating processes, and the number of repetitions is determined according to the required thickness of the phase change film.
[0068] (5) Peeling:
[0069] Prepare the chemical agents such as N-methylpyrrolidone (NMP), isopropyl alcohol (IPA) and ultrapure water required for stripping. Soak the substrate with the phase change material deposited in (3) in the NMP solution, and use an ultrasonic cleaner for 1 minute to strip off the excess photoresist 4 and phase change material on the substrate to obtain a patterned phase change material. Then soak the patterned phase change material in an IPA solution and ultrapure water for 2 minutes to remove the residual NMP solution, and the stripping step is completed. Finally, Figure 2 The structure of step (5) in .
[0070] Example 4
[0071] A method for preparing an improved phase change material structure comprises the following steps:
[0072] (1) Cleaning the substrate:
[0073] Prepare an ordinary glass sheet with a size of 20mm*20mm*0.5mm, place the ordinary glass sheet in containers containing acetone, ethanol, and ultrapure water in turn, and ultrasonicate them in an ultrasonic cleaning machine for 20 minutes (ultrasonicate for 20 minutes in all three media) to remove impurities on the ordinary glass sheet, and the cleaning of the substrate layer 3 is completed.
[0074] (2) Design of phase change material layer 2: Based on the required thickness of the phase change material film, 65 nm is used as the limit: when it is less than 65 nm, there is no need to divide the thickness; when it exceeds 65 nm, the film is divided into equal thicknesses to form a phase change material layer 2, so that the thickness of the phase change material layer 2 does not exceed 65 nm, and the dielectric film layer 1 is used to fill the space between the phase change material layers 2;
[0075] (3) Deposition of phase change materials and dielectric films:
[0076] Preparation of phase change material Sb 2 Se 3 Target material, Sb deposition by sputtering 2 Se 3 The film was placed on a cleaned ordinary glass substrate with a vacuum degree of 8.0×10 -4 Pa, the argon flow rate during deposition is 30sccm, the pressure is 1Pa, the power is 80W, and the deposition rate is about The deposition thickness is about 100 nm, and the phase change material deposition is completed.
[0077] Electron beam evaporation was used to deposit Sb 2 Se 3 TiO deposited on the film surface 2 The vacuum degree during deposition is 8×10 -4 Pa, the deposition thickness is about 20nm. The dielectric film deposition is completed. Repeat the above two coating processes, and the number of repetitions is determined according to the required thickness of the phase change film; finally, the following is formed: Figure 1 The structure shown.
[0078] Example 5
[0079] A method for preparing an improved phase change material structure, such as Figure 3 The following steps are shown:
[0080] (1) Cleaning the substrate:
[0081] Prepare a substrate coated with an ITO film, a circular substrate with a diameter of 25.4 mm and a thickness of 0.55 mm, place the ITO substrate in containers filled with acetone, ethanol, and ultrapure water in turn, and ultrasonicate them in an ultrasonic cleaning machine for 20 minutes (ultrasonicate for 20 minutes in all three media) to remove impurities on the ITO substrate, and the cleaning of the substrate layer 3 is completed.
[0082] (2) Design of phase change material layer 2: Based on the required thickness of the phase change material film, 65 nm is used as the limit: when it is less than 65 nm, there is no need to divide the thickness; when it exceeds 65 nm, the film is divided into equal thicknesses to form a phase change material layer 2, so that the thickness of the phase change material layer 2 does not exceed 65 nm, and the dielectric film layer 1 is used to fill the space between the phase change material layers 2;
[0083] (3) Deposition of phase change materials and dielectric films:
[0084] Preparation of phase change material Sb 2 S 3 and Sb 2 Se 3 Mixed powder, Sb deposited by thermal evaporation 2 S 3 and Sb 2 Se 3 The mixed film was deposited on the cleaned ITO substrate with a vacuum degree of 8.0×10 -4 Pa, the deposition rate is about The deposition thickness is about 70nm, and the phase change material deposition is completed.
[0085] Atomic layer deposition (ALD) was used to deposit Sb 2 S 3 and Sb 2 Se 3 200 layers of ZnS (about 12 nm) were deposited on the surface of the mixed film. The vacuum degree during deposition was 0.5 Pa, the substrate temperature was 200 °C, and the reaction precursor used was diethyl zinc (Zn(C 2 H 5 ) 2 ) and hydrogen sulfide (H 2 S), the deposition of a single layer of ZnS takes about 2 minutes, and the dielectric film deposition is completed. Repeat the above two coating processes, and the number of repetitions is determined according to the required thickness of the phase change film.
[0086] (4) Make a pattern:
[0087] Prepare chemical agents such as photoresist, developer, and fixer. Use a coating machine to spin-coat the photoresist (negative photoresist, AR-N 4240) on the cleaned ITO substrate at 3000 rpm. Through the process steps of photolithography, development, and fixation, a photoresist pattern with a specific structure is obtained, and the pattern production is completed.
[0088] (5) Etching:
[0089] The sample with the photoresist pattern prepared in (3) is placed in a plasma etcher, and the photoresist pattern is used as a mask to etch out the patterned phase change material, and the etching step is completed.
[0090] (6) Peeling:
[0091] Prepare chemical agents such as acetone, isopropyl alcohol (IPA) and ultrapure water. Soak the etched sample in the adhesive remover solution for 2 minutes to remove the residual photoresist; then soak the sample in IPA solution and ultrapure water for 2 minutes to remove the residual adhesive remover, and the stripping step is completed; finally, Figure 3 The structure shown in step (5) in .
[0092] Comparative Example
[0093] A 130nm thick Sb layer was deposited by thermal evaporation. 2 S 3 After heating and crystallization, the film shows anisotropic grains (different colors) under orthogonal polarized light. The picture taken under a microscope is as follows Figure 4 shown.
[0094] In any of the embodiments 2 to 5 of the present application, the phase change material film is layered and SiO2 is deposited in the middle by magnetron sputtering. 2 After the film is isolated, the grain size of the crystallized film is greatly reduced and randomly distributed. The statistical average effect can be considered that the refractive index of the film is uniform. The image of the specific phase change material taken under a microscope is as follows: Figure 5 As shown, Figure 5 The phase change material is 130nm thick Sb 2 S 3 The film is divided into two single layers of 65nm thick Sb 2 S 3 Thin film, 25nm thick SiO 2 Multilayer film system for thin film isolation.
[0095] The layering strategy proposed in this invention is independent of the film area, so a centimeter-scale uniform refractive index region can be achieved, which can meet the application requirements of most PCMs photonic devices. Finally, the strategy proposed by us does not require expensive and complex single crystal growth process conditions. A large area of uniform refractive index region can be obtained by simply layering the PCMs film, which greatly reduces the production and preparation costs of PCMs devices.
[0096] The above embodiments are merely examples of the present invention and do not limit the protection scope of the present invention. All designs that are the same or similar to the present invention fall within the protection scope of the present invention.
Claims
1. An improved phase change material structure, characterized in that: It includes a substrate layer, a phase change material layer and a dielectric film layer; the phase change material layer is located above the substrate layer, the dielectric film layer is located above the phase change material layer, and when the thickness of the phase change material layer is higher than 65nm, the phase change material layer is layered, and the dielectric film layer is filled between the layered phase change material layers; the total thickness of the phase change material layer is 0-5000nm; the thickness of each dielectric film layer is 0-5000nm.
2. The improved phase change material structure according to claim 1, characterized in that: The substrate layer is one or more of an ordinary glass sheet, a fused quartz sheet, a single crystal silicon sheet, and a substrate coated with a thin film.
3. The improved phase change material structure according to claim 1, characterized in that: The phase change material layer is a mixture or compound consisting of two or more elements of Sb, S, and Se.
4. The improved phase change material structure according to claim 3, characterized in that: The phase change material layer further includes an X element, and the X element includes one or more elements of In, Bi, Ag, Al, Zn, Co, Ni, Cu, Sn, O, Ge or Te.
5. The improved phase change material structure according to claim 1, characterized in that: The material of the dielectric film layer is one or more of oxide, nitride or sulfide.
6. The improved phase change material structure according to claim 5, characterized in that: The material of the dielectric thin film layer is one or more of Al2O3, SiO2, Ta2O5, ZrO2, TiO2, HfO2, tin-doped indium oxide, aluminum-doped zinc oxide, ZnS, TiN or Si3N4.
7. A method for preparing an improved phase change material structure, characterized in that: The following steps are involved: (1) Cleaning the substrate: preparing a substrate layer, placing the substrate layer in containers containing acetone, ethanol, and ultrapure water in turn for ultrasonic cleaning to remove impurities on the substrate layer; (2) Phase change material layer design: The number of phase change material layers is designed according to the thickness of the phase change material film. When the thickness of the phase change material film exceeds 65 nm, the phase change material film is layered to obtain a layered phase change material layer; (3) Depositing a phase change material layer and a dielectric film layer according to the design of the phase change material layer: using chemical vapor deposition or physical vapor deposition to alternately deposit phase change material layers and dielectric film layers on the cleaned substrate, and a dielectric film layer is provided on top of each phase change material layer, the thickness of each phase change material layer does not exceed 65nm, the total thickness of the phase change material layer is 1-5000nm, and the thickness of each dielectric film layer is 1-5000nm.
8. A method for preparing an improved phase change material structure, characterized in that: The following steps are involved: (1) Cleaning the substrate: preparing a substrate layer, placing the substrate layer in containers containing acetone, ethanol, and ultrapure water in turn for ultrasonic cleaning to remove impurities on the substrate layer; (2) Patterning: Spin-coating the photoresist on the cleaned substrate layer with a coating machine, and exposing or photolithography the photoresist on the substrate layer through an electron beam exposure or photolithography process to obtain a pattern with a specific structure; (3) Phase change material layer design: The number of phase change material layers is designed according to the thickness of the phase change material film. When the thickness of the phase change material film exceeds 65 nm, the phase change material film is layered to obtain a phase change material layer. (4) Depositing a phase change material layer and a dielectric film layer according to the design of the phase change material layer: using chemical vapor deposition or physical vapor deposition to alternately deposit phase change material layers and dielectric film layers on a patterned substrate layer, and providing a dielectric film layer on top of each phase change material layer, wherein the thickness of each phase change material layer does not exceed 65 nm, the total thickness of the phase change material layer is 1-5000 nm, and the thickness of each dielectric film layer is 1-5000 nm; (5) Stripping: Prepare the debonding agent, isopropyl alcohol and ultrapure water required for stripping, immerse the substrate on which the phase change material is deposited in step (3) in the debonding agent, and ultrasonically strip off the excess photoresist and other process residues on the substrate layer in an ultrasonic cleaning machine to obtain a patterned phase change material; then immerse the patterned phase change material in an isopropyl alcohol solution and ultrapure water in turn to remove the residual debonding agent solution.
9. A method for preparing an improved phase change material structure, characterized in that: The following steps are involved: (1) Cleaning the substrate: preparing a substrate layer, placing the substrate layer in containers containing acetone, ethanol, and ultrapure water in turn for ultrasonic cleaning to remove impurities on the substrate layer; (2) Design of phase change material layer: Design the number of phase change material layers according to the thickness of the phase change material film. When the thickness of the phase change material film exceeds 65 nm, the phase change material film is layered to obtain a phase change material layer. (3) Depositing a phase change material layer and a dielectric film layer according to the design of the phase change material layer: using chemical vapor deposition or physical vapor deposition to alternately deposit phase change material layers and dielectric film layers on the cleaned substrate, and a dielectric film layer is provided on top of each phase change material layer, the thickness of each phase change material layer does not exceed 65 nm, the total thickness of the phase change material layer is 1-5000 nm, and the thickness of each dielectric film layer is 1-5000 nm; (4) Patterning: Spin-coating a photoresist onto a substrate layer on which a phase change material layer and a dielectric film layer are deposited using a coating machine, and exposing or photolithography the photoresist on the substrate layer by electron beam exposure or photolithography to obtain a pattern having a specific structure; (5) Etching: using the photoresist pattern produced in step (4) as a mask, and performing an etching process to obtain a patterned phase change material; (6) Stripping: Prepare the debonding agent, isopropyl alcohol and ultrapure water required for stripping, immerse the substrate on which the phase change material is deposited in step (5) in the debonding agent, and ultrasonically strip off the excess photoresist and other process residues on the substrate layer in an ultrasonic cleaning machine to obtain a patterned phase change material; then immerse the patterned phase change material in an isopropyl alcohol solution and ultrapure water in turn to remove the residual debonding agent solution.
10. The method for preparing any one of the improved phase change material structures according to claim 7, 8 or 9, characterized in that: The dielectric thin film layer is deposited by chemical vapor deposition or physical vapor deposition; Chemical vapor deposition and physical vapor deposition methods include: atmospheric pressure chemical vapor deposition, low pressure chemical vapor deposition, plasma enhanced chemical vapor deposition, metal organic chemical vapor deposition, photochemical vapor deposition, atomic layer deposition, evaporation or ion plating.
Citation Information
Patent Citations
Method of improving phase change material
CN112736197A
